Species-Specific Identification from Incomplete Sampling: Applying DNA Barcodes to Monitoring Invasive Solanum Plants - Zhang, Wei (Public Library of Science, 2013)
Comprehensive sampling is crucial to DNA barcoding, but it is rarely performed because materials are usually unavailable. In practice, only a few rather than all species of a genus are required to be identified. Thus identification of a given species using a limited sample is of great importance in current application of DNA barcodes. Here, we selected 70 individuals representing 48 species from each major lineage of Solanum, one of the most species-rich genera of seed plants, to explore whether DNA barcodes can provide reliable specific-species discrimination in the context of incomplete sampling. Chloroplast genes ndhF and trnS-trnG and the nuclear gene waxy, the commonly used markers in Solanum phylogeny, were selected as the supplementary barcodes. The tree-building and modified barcode gap methods were employed to assess species resolution. The results showed that four Solanum species of quarantine concern could be successfully identified through the two-step barcoding sampling strategy. In addition, discrepancies between nuclear and cpDNA barcodes in some samples demonstrated the ability to discriminate hybrid species, and highlights the necessity of using barcode regions with different modes of inheritance. We conclude that efficient phylogenetic markers are good candidates as the supplementary barcodes in a given taxonomic group. Critically, we hypothesized that a specific-species could be identified from a phylogenetic framework using incomplete sampling–through this, DNA barcoding will greatly benefit the current fields of its application.